Impact of STEAM Education on Creativity Development in Science Classrooms: Perception of High School Students - Hafsa Qayyum; Bushra Mustafa Kamal* (Dialogue Social Science Review (DSSR), 2025)
This survey-based study explored the perceptions and practices of 120-150 senior school students in Multan, Pakistan, regarding STEAM (Science, Technology, Engineering, Arts, and Mathematics) education. Using a simple random sampling technique, data were collected from students across various academic disciplines, including Arts and Humanities, Education, Social Sciences, Science-technology & engineering, computer sciences, management sciences,Medical and Health sciences. A 17-item questionnaire based on a 5-point Likert scale measured three categories: Awareness (2 dimensions), Perception (8 dimensions), and Implementation (4 dimensions). The findings revealed that most students held positive views about the benefits of STEAM education. Over 70% believed it enhances critical thinking, deepens understanding, supports a constructivist approach, and improves professional competence. Students also acknowledged STEAM’s role in promoting aesthetic awareness and a holistic learning experience. However, despite these positive perceptions, a significant gap was observed in the actual implementation of STEAM practices. Teaching methods and classroom activities were not aligned with STEAM principles, indicating a lack of structured integration in the learning environment. The study highlights the need for improved planning and application of STEAM approaches to fully realize their potential in educational settings.